Pengaruh Penggunaan Smartphone Dalam Interaksi Sosial di Kalangan Mahasiswa Manajemen STIE Bina Karya Kota Tebing Tinggi - Kumala Vera Dewi; Bobby Hartanto; Adrian K. Tarigan (Digital Business Progress, 2023)
This study aims to determine the effect of smartphone use on social interaction in Management Study Program students at STIE Bina Karya, Tebing Tinggi City. The population of this study were 253 students in the third semester of the Management Study Program at STIE Bina Karya, Tebing Tinggi City. After calculating using the Slovin formula, the number of samples obtained is 72 respondents (with e = 10%). The data collection technique used was a questionnaire given to research respondents. The data analysis used in this study is a simple linear regression analysis with the help of SPSS for windows software. The results showed that there was no significant influence between the use of smartphones on social interaction among third semester students of the Management Study Program at STIE Bina Karya, Tebing Tinggi City. This means that no matter how long students use smartphones, it will not affect their social interactions with other people. The level of influence of smartphone use with social interaction among students in this study was very small, namely 3.2%. This is because social interaction is not only influenced by dependence on smartphone use, one of which can be influenced by community environmental factors.